VUV photodissociation of DNCO: dynamics of the D atom elimination channel. (17th January 2021) - Xie, Ting; Su, Shu; Yu, Shengrui; Luo, Zijie; Chen, Zhichao; Wang, Xingan; Yuan, Kaijun; Yang, Xueming
Abstract : The D atom Rydberg tagging time-of-flight technique was applied to investigate the photodissociation dynamics of DNCO in the vacuum ultraviolet 133–137 nm region. The D atom product was detected and the corresponding product translational energy distributions and angular distributions were obtained. Three product channels, D + NCO(X 2 Π), D + NCO(A 2 Σ + ) and D + NCO(B 2 Π), which arise from different dissociation pathways have been observed. It is found that the D + NCO(X 2 Π) channel involves two different dissociation pathways; one is via internal conversion from the excited state to the S0 state, and the other is via internal conversion from the excited state to the S1 state. The D + NCO(A 2 Σ + ) channel was ascribed to be from dissociation on S2 surface, and the D + NCO(B 2 Π) channel possibly come from a relatively slow dissociation process. Vibrational structures observed in the D + NCO(A 2 Σ + ) channel shows that there is dominant bending with a little stretching vibrational excitation of NCO(A 2 Σ + ). This is consistent with what has been found in the previous study following VUV photodissociation of HNCO in a similar wavelength region. GRAPHICAL ABSTRACT: